Employee Performance in Enhancing Public Service Delivery in Mendawai District, Katingan Regency - Suroyo Siswo Raharjo; Annisa Rahmadanita; Agung Nurrahman (Institut Pemerintahan Dalam Negeri, 2025)
This research was conducted to address the complaints from the community regarding public services at Mendawai District Office, Katingan Regency, highlighting the need to improve employee performance. The research aims to provide an overview of employee performance in enhancing public services and employs a quasi-qualitative method, collecting primary data through observation, interviews, and documentation. The findings indicate that employee performance is influenced by five key factors: quality, quantity, effectiveness, timeliness, and interpersonal relationships. Challenges identified include a shortage of human resources and uneven participation in technical guidance and training, resulting in some employees delivering services without adequate skill development. Despite these challenges, public services in Mendawai District have generally been functioning well. The research recommends increasing the number of employees in line with actual needs, providing regular technical guidance and training, and ensuring sufficient budget allocation to support public service activities, thereby improving overall service quality and employee performance.